THE IMPACT OF ALGERIAN RESEARCHERS TOWARDS NATIONAL RESEARCH AND ITS IMPACT ON THE IMPACT FACTOR OF SCIENTIFIC JOURNALS - Meryem HADDAD (Analele Universităţii din Craiova. Psihologie, Pedagogie)
The present study aims to explore the causes of the decreasing impact factor of Algerian journals published on the ASJP platform. Our analysis corpus consists of 51 articles from the journal Action Didactique, published during the years 2022 and 2023. The objective is to analyze the algorithms provided by ResearchGate, Google Scholar to calculate its true impact factor through citation analysis. The bibliometric analysis suggests a significantly higher impact factor than that displayed on the national platform. The research findings reveal that one of the main causes of the decrease in the impact factor of Action Didactique is the tendency of Algerian researchers to focus on foreign works at the expense of national ones. The study proposes editorial alternatives to improve the journal’s visibility.